2020
DOI: 10.1002/ehf2.13084
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the characteristics and outcomes of patients hospitalized with acute decompensated heart failure admitted to internal medicine and cardiology departments: a single‐centre, retrospective cohort study

Abstract: Aims Efforts are constantly made to decrease the rates of readmission after acute decompensated heart failure (ADHF). ADHF admissions to internal medicine departments (IMD) were previously associated with higher risk for readmission compared with those admitted to cardiology departments (CD). It is unknown if the earlier still applies after recent advancement in care over the last decade. This contemporary cohort compares characteristics and outcomes of ADHF patients admitted to IMD with those admitted to CD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…In agreement with the findings by Mayman et al on HF patients admitted to Internal Medicine units, the mean age of the patients is much higher than those included in clinical trials and even in community-based studies on ADHF [18]. HFpEF patients represent over 50% of the entire cohort, indicating, as previously reported, that the two HF phenotypes are at least equally prevalent among hospitalized patients [19,20].…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with the findings by Mayman et al on HF patients admitted to Internal Medicine units, the mean age of the patients is much higher than those included in clinical trials and even in community-based studies on ADHF [18]. HFpEF patients represent over 50% of the entire cohort, indicating, as previously reported, that the two HF phenotypes are at least equally prevalent among hospitalized patients [19,20].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, in the current study, the number of patients ≥85 years and their mean age is higher than that analyzed in previous reports, either in Italy or Europe [5,13,16]. Furthermore, at odds with previous studies based on registries and surveys [5,19], we considered exclusively patients admitted to internal medicine wards as it has been documented that those admitted to cardiology units are a selected group of younger patients with significant differences in clinical characteristics and outcomes, in Italy and elsewhere [20,21].…”
Section: Discussionmentioning
confidence: 83%
“…We were able to perform the meta-analysis for three domains of the SCHFI: con dence, maintenance and management. A total of 34 primary studies were pooled to calculate the overall effect size of comorbid conditions on prognostic outcomes: in-hospital mortality (21,23,26,29,32,33,40,57), all-cause mortality (18, 19, 24-27, 36, 37, 43, 47, 48, 50, 51, 55, 57-59), all-cause readmission (27,28,30,32,34,37,38,41,44,45,55,58), HF-related readmission (20,28,35,37,51,53,57), non-HF-related readmission (28, 53) and delayed length of hospital stay (23,32). Among the prognostic outcome measures, all-cause mortality was the only measure with su cient data for the meta-analysis based on the follow-up periods.…”
Section: Quantitative Analysesmentioning
confidence: 99%
“…The pooled analysis of 18 studies (18, 19, 24-27, 31, 36, 37, 43, 47, 48, 50, 51, 55, 57-59) indicated that HF patients with comorbidity had a statistically higher risk of all-cause mortality (HR 1.31, 95% CI 1.18, 1.45, p < 0.001). In addition, the presence of comorbidity signi cantly increased the risk of all-cause readmission (HR 1.16, 95% CI 1.09, 1.23, p < 0.001) (27,28,30,32,34,37,38,41,44,45,55,58), HF-related readmission (HR 1.13, 95% CI 1.05, 1.23, p = 0.001) (20,28,35,37,51,53,57) and non-HF-related readmission (HR 1.17, 95% CI 1.07, 1.27, p < 0.001) (28, 53). However, no signi cance was noted for in-hospital mortality and longer length of hospital stay (Fig.…”
Section: Overall Effects Of Comorbidity On Hf Outcome Measuresmentioning
confidence: 99%